The Impact of Social Media Marketing on Digital Service Adoption in Educational Institutions: Exploring the Mediating Role of Brand Equity, Trust, and Word-Of-Mouth Advertising - Hosna Khorsandi; Behzad Kazemi; Simin Zeynali; Mahsa Mohsenibeigzadeh; Pedram Zarei; Shahin Mirshekari (Tehnički Glasnik)
Recently, educational institutions have turned to investing in new technologies to provide digital services to customers as a means of cost control, attracting new customers, and meeting customer expectations. The adoption of these new technologies has become crucial for these institutions as part of their strategy. Therefore, this research focuses on investigating the influence of social media marketing (SMM) on the intention to use digital services in educational institutions. The study also considers brand equity, trust, and word-of-mouth promotion as potential factors mediating this relationship. The method employed was descriptive correlational research, utilizing structural equation modeling for data analysis, with 368 students participating. The results indicate that SMM has a significant influence on brand equity, trust, word-of-mouth advertising, and the intention to utilize digital services in educational institutions. Furthermore, brand equity, trust, and word-of-mouth advertising exert a positive and significant impact on the intention to use digital services within educational institutions. Additionally, brand equity, trust, and word-of-mouth advertising act as vital mediators in the relationship between SMM and the adoption of digital services in educational institutions. Consequently, we can conclude that SMM contributes to an increased intention to use digital services in educational institutions by leveraging brand equity, trust, and word-of-mouth advertising.